Natural microbial exposure populates the maternal fetal interface with diverse T cells - Whillock, Amy; Smith, Perianne; Burger, Sarah; Sridhar, Adhvaith; Lindgren, Alex; Berg, James; Tsuda, Sayaka; Mahajan, Shweta; Tilburgs, Tamara; Schuldt, Nathaniel J. (Frontiers in Immunology, 2025)
Diverse T cell types accumulate at the human maternal fetal interface (MFI) during pregnancy to orchestrate immune tolerance for foreign fetal/placental tissues and immunity to pathogens. Yet, the dynamics of T cell influx and function at the MFI remain poorly defined. Conventional specific pathogen free (SPF) murine models fail to replicate the number and diversity of T cells in the human MFI, hindering mechanistic study of MFI T cells. Here we present an innovative use of a natural microbial exposure (NME) mouse model that enhances T cell influx and diversity in the MFI. We defined changes in the MFI of NME mice, relative to SPF mice and human tissues using transcriptomic and proteomic approaches. Physiological maternal microbial burden reproduced key features of human MFI immunology by i) significantly increasing the numbers and diversity of CD4 and CD8 effector and memory T cells at the MFI; ii) skewing the CD8 T cell composition towards tissue resident memory phenotypes with increased signatures of activation and dysfunction similar to human decidual T cells; and iii) expanding unconventional γδ T cells and Killer Lectin-like Receptors (KLR) expressing T cell types at the MFI, representative of an enhanced ability to interact with placental trophoblasts or infected cells. Thus, maternal microbial exposure induces vast changes to T cell numbers, diversity and functions at the MFI that models human MFI T cells with great fidelity. The NME model allows for improved translational investigation of the mechanisms of T cell tolerance, immunity, and inflammation in pregnancy.